Development and validation of a prognostic model for patients with cT1-4N1-3M1 esophageal squamous cell carcinoma: based on the SEER database and the Chinese cohort study - Wang, Xiao-Mei; Liu, Can-Tong; Huang, Jia-Tao; Zhang, Zhi-Han; Xu, Yi-Wei; Wu, Fang-Cai; Peng, Yu-Hui (Frontiers in Oncology, 2025)
ObjectiveThe purpose of this study was to investigate the impact of clinicopathological factors on the overall survival (OS) of advanced esophageal squamous cell carcinoma (ESCC) patients with both lymph node and distant metastasis and build a nomogram for OS prediction.MethodWe selected 621 ESCC patients with cT1-4N1-3M1 stage without surgical treatment from the Surveillance, Epidemiology, and End Results (SEER) database and randomized (in a 7:3 ratio) to the training cohort and internal validation cohort. Another 159 patients were enrolled from the Cancer Hospital of Shantou University Medical College as the external validation cohort. A nomogram was developed based on independent risk factors that resulted from a multivariate Cox regression analysis. Receiver operating characteristic (ROC) curves and the area under the ROC curve (AUC) were used to evaluate the discriminative ability and calibration curves were constructed to evaluate the calibration ability. Kaplan-Meier survival analysis and log-rank tests were then used to predict the further OS status of these patients.ResultsThe multivariate Cox regression analysis revealed that sex, T stage, radiotherapy, and chemotherapy were independent prognostic factors for ESCC patients with cT1-4N1-3M1 stage. All these factors were incorporated to construct a nomogram. The prognostic nomogram in training cohort exhibited the AUCs of 0.784, 0.746, and 0.735 for predicting 6-, 9-, and 12-month OS, respectively. Calibration curves exhibited that the nomogram-predicted OS were insistent with the actual OS. In validation cohorts, the nomogram still showed acceptable discrimination ability and calibration. All individuals were allocated into high-risk versus low-risk groups based on the median risk score of the training cohort. The OS of the high-risk group was shorter than that of the low-risk group in three cohorts.ConclusionWe developed and validated an individualized survival prediction nomogram for predicting OS in ESCC patients with cT1-4N1-3M1 stage, which may help clinicians to assess the situation of advanced ESCC patients and implement further treatment.